Indonesia Islamic Banking Stability in The Shadow of Covid-19 Outbreak - Sintia Dewi Nur Ajizah; Agus Widarjono (Universitas Airlangga, 2023)
ABSTRACT: The Covid-19 pandemic that has occurred in the world has harmed economies since 2020, especially Indonesia. Therefore, it is very important to study the impact of this pandemic on the stability of Islamic banking in Indonesia and examine potential signs of post-pandemic recovery. This study examines the stability of Islamic banking in Indonesia. Stability is measured using ROA and Z-score. The data in this study are panel data for Islamic Commercial Banks (BUS) and Islamic Business Units (UUS). The data used is quarterly data for 2016-2020. This study uses the Generalized Method of Moment (GMM). The results of this study are ROA for Assets, CAR, FDR, and Covid-19 do not affect profits. However, NPF and BOPO have a negative effect. Whereas on the Z-score for Assets, CAR FDR has a positive effect. NPF and BOPO harm the stability of Islamic banking, except for Covid-19. Lower efficiency and problematic financing reduce the stability of Islamic banking. In addition, the results of our analysis, based on profitability and financial stability during the quarterly period, Islamic banking was able to survive during the Covid-19 pandemic. This research implies that even though some variables do not significantly affect profits, Islamic banks must still pay attention to other variables, such as ROA, owned assets, CAR, FDR, and Covid-19 which are likely to have a large negative impact on the long term. Apart from that, Islamic banks must also maintain profits and stability to survive and compete with conventional banking amid the Covid-19 pandemic. Keywords: Generalized Method of Moment, Islamic Bank, Banking Stability, Return on Assets, Z Score ABSTRAK: Pandemi Covid-19 yang terjadi di dunia memberikan dampak negatif bagi perekonomian sejak tahun 2020, khususnya Indonesia. Oleh karena itu, sangat penting untuk mengkaji dampak pandemi terhadap stabilitas perbankan syariah di Indonesia dan mengkaji potensi pemulihan pasca pandemi. Penelitian ini mengkaji tentang stabilitas perbankan syariah di Indonesia. Stabilitas diukur menggunakan ROA dan Z-score. Data dalam penelitian ini adalah data panel untuk Bank Umum Syariah (BUS) dan Unit Usaha Syariah (UUS). Data yang digunakan adalah data triwulanan tahun 2016-2020. Penelitian ini menggunakan Generalized Method of Moment (GMM). Hasil penelitian ini adalah ROA untuk Aset, CAR, FDR, dan Covid-19 tidak berpengaruh terhadap keuntungan perbankan syariah. Namun NPF dan BOPO berpengaruh negatif. Sedangkan pada Z-score untuk Aset, CAR FDR berpengaruh positif. NPF dan BOPO berpengaruh negatif terhadap stabilitas perbankan syariah, kecuali Covid-19. Efisiensi yang lebih rendah dan pembiayaan bermasalah mengurangi stabilitas perbankan syariah. Selain itu, hasil analisis, berdasarkan profitabilitas dan stabilitas keuangan selama periode triwulanan, perbankan syariah mampu bertahan selama pandemi. Hasilnya menunjukkan implikasi bahwa meskipun beberapa variabel tidak berpengaruh signifikan terhadap keuntungan, namun Bank Syariah harus tetap memperhatikan variabel lain, seperti ROA, Aset yang dimiliki, CAR, FDR, dan Covid-19 yang kemungkinan akan terjadi dampak negatif yang besar dalam jangka panjang. Selain itu, Bank Syariah juga harus mampu menjaga keuntungan dan stabilitas agar mampu bertahan dan bersaing dengan perbankan konvensional di tengah pandemi. Kata Kunci: Generalized Method of Moment, Perbankan Islam, Stabilitas Keuangan, Return on Assets, Z Score REFERENCES Abbas, F., Iqbal, S., & Aziz, B. (2019). The impact of bank capital, bank liquidity and credit risk on profitability in postcrisis period: